Study of the effectiveness of stalls provided by MPMBB in Batu Berendam area / Julia Abu Bakar - Abu Bakar, Julia (Faculty of Business and Management, 2002)
Effectiveness of stalls provided by MPMBB is one of the factors that are being prioritized by the customers. The research is carried out to find out the effectiveness of stalls provided by MPMBB. The objectives of the study are (1) to identify the factors determining the effectiveness of the stall provided by MPMBB (2) to identify the main problems facing the owners of the MPMBB stalls (3) to determine the factors influencing the success of the stalls. This project paper consists of five chapters , which brings its own exploration of the topic being investigated. Chapter one is a comprehensive discussion about the company and background of the study. Chapter two is the literature review where the topic and related matters are explain in the marketing terms. Its explanation is related to the subject being studied. Chapter three is the research methodology and design. It is the explanation of the methods used in the research to gather the related information, which related to the study, the sampling technique, survey instruments and method used to analyze the data. Chapter four contains the findings of the study, The findings of the study are also discussed with regards to the problem statements and objectives of the study. Chapter five contains the conclusions and recommendations derived from the research. Appendices and bibliography attached are relevant references and list of books used for references in the study.